1983
DOI: 10.1104/pp.72.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytokinin-Regulated Responses by Calmodulin-Binding Compounds

Abstract: Two classes of compous which bind to calnodulin in a calciumdependent manner (neuroleptic drugs and local anaesthetics) were used to investigate the possible involvement of a calcium-dependent regulator protein in the action of the plant hormones cytokinins.The cytokinin-induced synthesis of betacyanin in Amarandus tricolr seedlings was used as one test system. The calmodulin antagonists inhibited betacyanin synthesis with the following order of potency: fluphenazine > trifluoperazine = pimozide > chlorpromazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The effect of auxin is seen at 3 h with inhibition by both TFP and TC becoming apparent by 6 h. In Figure 4, Inhibitor Concentration (mM) Table I with those already described for two other cytokinindependent systems and for the red light-stimulated betacyai synthesis in Amaranthu1s seedlngs (12,13 fusicoccin-stimulated growth, acid secretion, and hyperpolarization of the potential difference. These experiments were over shorter time periods than those reported here, but the tendency for stimulation at low concentrations followed by inhibition at high concentrations has been noted in a number of systems (12,13, and this paper, Figs. 1, 2, 4, and 5; Table II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of auxin is seen at 3 h with inhibition by both TFP and TC becoming apparent by 6 h. In Figure 4, Inhibitor Concentration (mM) Table I with those already described for two other cytokinindependent systems and for the red light-stimulated betacyai synthesis in Amaranthu1s seedlngs (12,13 fusicoccin-stimulated growth, acid secretion, and hyperpolarization of the potential difference. These experiments were over shorter time periods than those reported here, but the tendency for stimulation at low concentrations followed by inhibition at high concentrations has been noted in a number of systems (12,13, and this paper, Figs. 1, 2, 4, and 5; Table II).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has followed the line that calcium interactions with cytokinins may mean that the calcium-dependent regulator protein calmodulin is involved. It was found that drugs which bind to calmodulin and inhibit its action in other systems do indeed inhibit betacyanin accumulation, whether induced by cytokinin, fusicoccin, or red light, and also another cytokinin-dependent response, cell division in soybean callus tissues (13).…”
mentioning
confidence: 99%
“…Blue-light inhibition of hypocotyl segment elongation showed a specific requirement for Ca" (23). Furthermore, calmodulin-binding compounds have been found to inhibit several cytokinin-regulated processes (8,9). An obvious question to ask, therefore, was whether or not Ca2+ is required in order for BA to inhibit hypocotyl growth.…”
Section: Preparation and Handling Of Segmentsmentioning
confidence: 99%
“…From this and other results, it is concluded that a control point for hormones and phytochrome is one which is affected in the same way by Ca2+-calmodulin inhibitors. Possibly, mutual regulation could be through plasma-membrane-bound ATPases [ 13].…”
Section: Calcium Action and Calmodulinmentioning
confidence: 99%